PECULIARITIES OF ANTIHYPERTENSIVE THERAPY INDICATED IN THERAPEUTIC AND SURGICAL DEPARTMENTS OF THE UNIVERSITY CLINICAL HOSPITAL - N. A. Morina; O. D. Savkova; E. A. Fedorova; I. L. Tsarev; A. B. Frolkova; A. E. Tsygankova; A. A. Sokolova; D. A. Napalkov; V. V. Fomin (Медицинский совет, 2017)
Treatment of arterial hypertension (AH) despite the large variety of antihypertensive drugs currently remains one of the most urgent problems in modern cardiology. However, the scheme used in clinical practice does not always correspond to existing recommendations, in particular, of the European Society of Hypertension, ESH, and the European Society of Cardiology, ESC. Thus, patients with 2–3 degree increase blood pressure (BP) and high or very high added risk often do not get the combination therapy that is required for them in this clinical environment. According to the recommendations of the ESH and ESC patients with hypertension of low/medium risk of development of cardiovascular complications (CVC) and death from them a monotherapy can be prescribed if targeted AP values are achieved [1]. Patients with high or very high risk of CCO and/or AG of Degree 2 and 3 immediately must be prescribed a combination of the two drugs. If the target blood pressure values are not attained, either a combination of two drugs at the maximum therapeutic doses, or replacement of the combination of drugs is prescribed or the 3d, 4th and so on antihypertensive drug is added [2, 3]. Combination therapy may also be administered to patients with hypertension with low/medium risk of development of CVC if the target AP are not reached [3, 4].